2015
DOI: 10.1002/pbc.25714
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Financial Burden as a Standard of Care in Pediatric Oncology

Abstract: Family financial hardship has emerged as a burden of pediatric cancer treatment with negative implications for family well‐being. As part of an extensive project to create evidence‐based standards for the psychosocial care of children with cancer, we performed a literature review of pediatric cancer‐associated financial hardship utilizing six databases, and identified 24 publications for incorporation into this review. Financial hardship during childhood cancer was found to affect a significant proportion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
164
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(170 citation statements)
references
References 35 publications
5
164
1
Order By: Relevance
“…Even after the end of successful treatment, some parents need to reduce working hours [4]. The literature, still scarce, indicates that family income decreases and expenses increase in the wake of childhood cancer [5]. In a previous study, we concluded that childhood cancer affects parents', particularly mothers', possibility to maintain working hours up to one year after completion of treatment [6], however, only minor adverse effects were found five years after end of treatment [7].…”
mentioning
confidence: 90%
“…Even after the end of successful treatment, some parents need to reduce working hours [4]. The literature, still scarce, indicates that family income decreases and expenses increase in the wake of childhood cancer [5]. In a previous study, we concluded that childhood cancer affects parents', particularly mothers', possibility to maintain working hours up to one year after completion of treatment [6], however, only minor adverse effects were found five years after end of treatment [7].…”
mentioning
confidence: 90%
“…To summarize, psychosocial support for families with a history of childhood cancer has positive effects for parents [9,10] and is recommended by international guidelines [4,6]. Such support not only help parents, but also their family members.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published guidelines for how children diagnosed with cancer and their family members should be cared for, recommend standardized psychosocial and financial risk assessments and referrals across the disease trajectory into long-term survivorship [4,6]. A substantial group of Swedish parents of children on cancer treatment reports a need to talk to psychologists, but few get the opportunity to do so [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians can work with other members of the health care team, such as social workers, to ensure that all families are assessed for financial hardship at the time of diagnosis, are reassessed regularly throughout treatment, and are referred appropriately. Referrals might be made to the hospital's financial counseling office, community organizations, and governmental programs [25]. Families may also require assistance navigating state and federal safety-net programs.…”
Section: Recognize the Financial Impact Of A Childhood Cancer Diagnosmentioning
confidence: 99%